(untitled) (UKH Journal of Social Sciences, 2022)
This research determines the impact of content marketing (user-generated content (UGC) and firm-generated content (FGC)) on the consumer buying process for telecommunication products and services in the Kurdistan Region of Iraq (KRI). The study attempts to compare the impact of UGC and FGC on the consumer buying process. To achieve this aim, the study utilized a descriptive quantitative methodology. The population of interest for this research is all consumers of telecommunication products in the KRI. Primary data was collected from 402 online questionnaires from a convenience, snowball, sample from the main provinces of Kurdistan. The results indicate that all FGC marketing dimensions have a statistically significant positive direct effect on the consumer buying process, while only content valence and information richness of UGC dimensions have a statistically significant positive direct effect. FGC valence has the greatest impact on the consumer buying process, closely followed by FGC trustworthiness, and then FGC information richness. Between the two examined types of content, FGC has a greater impact than UGC on the consumer buying process for telecommunication products and services. Telecommunications marketers and management should thus prioritize the identified FGC dimensions in their marketing strategies for optimum resource allocation efficiency. Further discussion is provided.